Radical innovation theory: towards radical design of digital workplaces - Lahti Marko; Nenonen Suvi; Sutinen Erkki; Pope Nicolas (Routledge, 2022)
Radical Innovation Theory is describing the rapid technological change in companies, organisations, and society. Technological evolution affects to the work environment too: workplaces are digital and physical entities Advances in technology and workplace design are making it possible to create workplaces that promote learning, discovery, social interaction, and engagement in various ways. This chapter is presenting the characteristics of radical innovation as well as describing the typology of innovations. More than that it is presenting a framework about workplace realities. This framework is a tool to classify the digital and physical workplace, their functionality and meaning. The research questions proposed are not only about radical innovation, but more about radical design of digital and physical workplaces.
A Handbook of Management Theories and Models for Office Environments and Services